ANALISA PENGARUH CORPORATE IMAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN DI SURABAYA - Aditya Ferryanto (Business Accounting Review, 2015)
The purpose of this study was to examine or test the affect of corporate image on financial performance through customer’s satisfaction as the intervening variable on bank companies in Surabaya. Sample of this study was 35 bank companies in Surabaya. Data were collected by distributing questionnaire to the consumen and got from Bursa Efek Indonesia. This study used path modeling analysis technique with PLS tools. Results showed that there were positive and significant affect of corporate image on customer’s satisfaction, positive and significant affect of customer’s satisfaction on financial performance, and also positive and significant affect of corporate image on financial performance on bank companies in Surabaya.